Comparison of Knowledge, Attitude and Practice of Urban and Rural Households toward Iron Deficiency Anemia in three Provinces of Iran - R Heshmat; B Azemati; AA Keshtkar; F Salehi; Z Abdollahi; F Kolahdouz; H PourAram; F Farivar; M Bagheri; R Sheykh-; A Nadim (Tehran University of Medical Sciences, 2009)
Background: Lack of nutritional knowledge is one of the most important reasons of nutritional problems and consequently improper practice, which can lead to several complications. This study has been designed in order to compare knowledge, attitude and practices of the urban and rural households regarding iron deficiency anemia (IDA) in Boushehr, Golestan and Sistan & Balouchestan provinces in 2004. Methods: The sampling method at household's level in each province was the single-stage cluster sampling with equal size clusters. The necessary data were gathered with a structured questionnaire and via the interviews between the questioners and the eligible people in each household. Comparison of frequency of variables between urban and rural areas were tested by chi square test. Results: A total of 2306 households were selected as overall sample size. In urban areas, people recognized iron food sources better than rural areas. Knowledge level of respondents about vulnerable group for IDA and the favorite attitude of households toward IDA were better in urban areas of Sistan & Blouchestan and Golestan provinces. In Sistan & Balouchestan and Golestan, rural households who drank tea immediately before or after meal was more than urban ones. The majority of pregnant and lactating mothers (except for rural areas of Bushehr) did not take iron supplement regularly. Less than 60 percent of children used iron drop regularly. Conclusion: Knowledge, attitude, and practice levels of households toward IDA were not acceptable. One of the best ways of improving nutritional practice is nutritional education with focus on applying available food resources.